Implementasi Pembayaran Upah Penggilingan Padi Dalam Perspektif Ekonomi Islam(Studi Kasus Di Penggilingan Padi Desa Rigangan Iii Kecamatan Kelam Tengah Kabupaten Kaur) - Nurantika Dwi Putri; Supardi Mursalin; Uswatun Hasanah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this research is to study the application of wage payments and Islamic economic perspectives to wage clearance in the village of Rigangan III, Kelam Tengah Prefecture, Kaur district. The research methods used are descriptive research and qualitative data analysis. The data collection methods applied include documentation, observation, and surveys. The results of this study show that in Rigangan III Village, Kelam Tengah Prefecture, Kaur District, wage payment system has become a common practice. In a scenario where farmers pick up their crops, wages are calculated on the basis of their amount, with the rate of 1 can of rice equivalent to 1 liter (6 cantings) of rice. Alternatively, if the landlord chooses to bring the crops directly to grinding, the wages will be measured as 1 can, which is equivalent of half a liter. (3 canting). 2) Islamic economic perspectives related to the implementation of the wages of grinding padi in the Village of Rigangan III, Kelam Tengah District, Kaur District, can be explained as follows: First, the determination of priorities is made according to the needs. Second, the application of the applicable law becomes consideration. Thirdly, wages are adjusted to time. Fourthly, wage rates are determined by seniority. Keywords:Wage, Islamic Economics,Rice Milling